Are there semantic false anglicisms? (Philology, 2026)
The article focuses on the nature of semantic developments in lexical borrowing (replication), proposing the discarding of the concept of “false-Xicization” in semantic adaptations of lexical replicas. Semantic shifting is recognized as an unavoidable, natural mechanism at the very heart of the process of lexical replication at the level of the individual bilingual user who carries over the replication.The life cycle of this neologism is not different in any way from native neologisms created by the mechanisms of semantic change or word formation. It is further hypothesized that the semantic development of a neological lexical replica in a receptor language expands and maintains an interlingual radial network of senses in the same manner that new senses do in the case of native radial networks of polysemous lexemes—with the exception of conceptual metaphor-driven new senses, which is an exclusively intralingual mechanism. In that sense, it can be claimed that interlingual semantic developments are no different than intralingual processes, which leads to the possibility of doing away with the concept of false-Xicization.
Keywords: semantic shifts; lexical replication; false-anglicisation; interlingual radial networks